Research on financing ecology and financing efficiency of strategic emerging industries in China - Xu, Ke; Geng, Chengxuan; Wei, Xiaoshu (Journal of Business Economics and Management, 2019)
After integrating external ecological and endogenous factors of the development of the industry, the paper builds a financing ecology index system, and analyses the financing ecology of strategic emerging industries in recent years. Then the paper further analyses the influence of external and internal financing ecology on financing efficiency. The results show that the financing ecology of the strategic emerging industries, external financing ecology in particular, is in the continuous improvement. The financing efficiency is significantly positively correlated with the macro-economy level and the internal financing ecology, and significantly negatively correlated with the role of government. There is a positive but non-significant correlation between financial development and financing efficiency, meanwhile a negative and non-significant correlation between credit environment and financing efficiency. The internal and external financing ecology can be replaced to some extent. Therefore, the strategic emerging industries should give full consideration to the synergistic optimization of the endogenous factors and external financing ecology so as to improve the financing efficiency.